Fats and oils : formulating and processing for applications - O'Brien, R. D. [ (Richard D.)] (CRC Press, 2009)
A comprehensive reference to fats and oils of commercial food products that provides detailed coverage of raw material sources, processing, formulation, quality control, and finished products. It features fresh processing procedures along with the effects of fresh ingredients, processing, and formulation on applications.